PELATIHAN KETERAMPILAN DASAR KOMPUTER DAN TEKNOLOGI INFORMASI BAGI SISWA - Putri, Prihastini Oktasari; Hidayati, Ika Septi; Febriana, Rina (Gemi: Jurnal Penelitian dan Pengabdian, 2024)
This devotion to public is motivated by the problem of students' lack of understanding in the use and application of computers at SD Negeri 1 Plumbon. The solution offered to address the partner's problem is to implement a community service program in the form of basic computer skills and information technology training for students. The objective of this community service is to provide knowledge and basic computer skills, as well as information technology, to elementary school students. The community service activities consist of four stages: 1) Planning stage, 2) Implementation stage, 3) Assistancetraining stage, and 4) Simulation and practice stage. Through this training, it aims to provide knowledge and basic computer skills, as well as information technology.